The Hirak. The Visual Performance of Diversity in Algerian Protests - Fedele, Valentina (PARTECIPAZIONE E CONFLITTO, 2021)
Based on the analysis of the first year of the Hirak, the Algerian protest movement started on February 2019, the article focuses on its visual performance and on the narrative emerging from it. Banners, posters and photos highlight the Hirak’s specific attempt to give a new meaning to the discourse about the Algerian people and its unity. Particular attention is given to the visual performance of Algerian diversity exemplified by the deployment of the Amazigh flag during the protests. The flag became more than a cultural symbol and represented an instance of freedom and a manifestation of the people’s will to escape traditional hetero-definitions of belongings and identities.